El rol de la avifauna en las técnicas artesanales tradicionales en la Parroquia Zumbahua - Pillajo Jumbo, Daniela Mishell (2022)
This research project is focused on the search for information on the role played by the avifauna in the traditional craft techniques of the Zumbahua parish, so the research began with the development of the first objective, which consists of developing an analysis of several main aspects such as; the sociocultural, socioeconomic, geographic, demographic, and tourist aspect of the community. Where it was evidenced that 98.8% of the total population of the inhabitants of the parish call themselves indigenous, while the difference in the population is called mestizos, it has a total of 13,764 inhabitants. The activities that belong to the primary sector and that generate a greater economic movement in the parish are agriculture, livestock and forestry that belong to 72.56% of the population, as part of the tertiary sector of the economy we have the craft activity and therefore to tourism that are linked hand in hand. All this analysis was given thanks to the primary and secondary information that was collected through the 5 field trips that were carried out with the research team, in addition to the bibliographic research tool that allowed us to search for information from various sources. As part of the second objective we have the preparation of the inventory; Within the parameters of the National Institute of Intangible Cultural Heritage, in the field of traditional craft techniques that are related to the avifauna of the parish, using various methods such as ethnography, which allowed researchers to approach the inhabitants of said community, it is say allowed us to interact with the main actors who were going to provide us with the necessary information for this project, through different tools such as recordings, photographs, videos and of course a questionnaire of questions to be able to carry out the interview, they were used in the same way forms the INPC tabs for area five. In the development of the investigation, it allowed to know the origin, the process and the cultural value, which are given to each of the crafts that are part of this investigation, as part of the analysis of results, it was concluded that there are five cultural manifestations that you are related to birds and their representation in handicrafts such as: the Condor, the Hummingbird, the Owl, the Eagle and the Curiquingue. For that, the following methodology was used: Ethnographic, inductive - deductive, descriptive and snowball method, which were helpful in being able to identify the key actors through referrals, as well as a questionnaire of questions to collect the information. Keywords: Crafts, Avifauna, Methodology, Techniques, Traditions.